2019
DOI: 10.1007/s00247-019-04463-9
|View full text |Cite
|
Sign up to set email alerts
|

Whole-body magnetic resonance imaging in paediatric Hodgkin lymphoma — evaluation of quantitative magnetic resonance metrics for nodal staging

Abstract: Background Whole-body MRI is used for staging paediatric Hodgkin lymphoma, commonly using size thresholds, which fail to detect disease in normal-size lymph nodes. Objective To investigate quantitative whole-body MRI metrics for nodal characterisation. Materials and methods Thirty-seven children with Hodgkin lymphoma underwent 1.5-tesla (T) whole-body MRI using short tau inversion recovery (STIR) half-Fourier-acquisition single-shot turbo-spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…For instance, health economy analysis has shown that for staging lung cancers, there is approximately 50% cost reduction for WB-MRI staging compared to standard staging pathway (including PET-CT) [ 24 ]. However, the majority of the published work either used a single morphological/functional sequence [ 22 ] or investigated the sequential added value of multiple sequences [ 10 , 12 , 15 ] as part of the WB-MRI protocol. Rarely in the literature has the diagnostic yield of each sequence been investigated separately for the evaluation of the same subject.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, health economy analysis has shown that for staging lung cancers, there is approximately 50% cost reduction for WB-MRI staging compared to standard staging pathway (including PET-CT) [ 24 ]. However, the majority of the published work either used a single morphological/functional sequence [ 22 ] or investigated the sequential added value of multiple sequences [ 10 , 12 , 15 ] as part of the WB-MRI protocol. Rarely in the literature has the diagnostic yield of each sequence been investigated separately for the evaluation of the same subject.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we were unable to obtain histological samples from all suspicious disease sites, as this would not be ethically and/or technically feasible, therefore we used an expert consensus panel and follow-up to derive an enhanced reference standard. Whilst such an approach is imperfect, it is often necessary for diagnostic accuracy studies [ 7 , 10 , 15 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A suggested SUV max cutoff for benign lymph nodes was less than 3.2. Diffusion-weighted imaging is helpful for identification of lymph nodes, although it does not outperform size criteria for characterization of malignant nodes (10)(11)(12).…”
Section: Clinical Applications Of Pet/mri In Children With Cancer and Neurofibromatosis Typementioning
confidence: 99%
“…WB-MRI outperforms PET/ CT in certain subtypes of lymphoma including peripheral Tcell lymphomas, indolent lymphomas, and lesions < 5 mm, as well as in patients presenting with a high extranodal disease load, because it allows for better evaluation of skeletal lesions including fracture risk assessments. 70,[72][73][74] Detection and Characterizations of Primary Skeletal Tumors…”
Section: Detection and Characterization Of Myeloproliferative Disordersmentioning
confidence: 99%